ANALISIS KUALITAS JASA KANGAROO PREMIER SHUTTLE TRAVEL SAMARINDA DENGAN MENGGUNAKAN MODEL KANO DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Dewi Sulistyowati (KINERJA, 2015)
The aim of this study was to determine the quality of services on Kangaroo Premier Shuttle Travel Samarinda to evaluate customer satisfaction, as well as to identify those attributes that need priority services to be improved. The technique of collecting data by distributing questionnaires. The total sample of 100 respondents using purposive sampling technique. The data analysis technique used is validity, reliability, Kano Model and Importance Performance Analysis (IPA). The results showed that the customers are satisfied with the performance of Kangaroo Premier Shuttle Travel, but the company needs to improve service performance to achieve higher satisfaction. Integration of Kano and Importance Performance Analysis (IPA) has eight attributes to be a priority in the improvement that can be made by the company.Keyword:   Quality of Service, Kano, Importance Performance Analysis (IPA)